Berberine Suppresses Influenza A Virus-Triggered Pyroptosis in Macrophages via Intervening in the mtROS-MAVS-NLRP3 Inflammasome Pathway - Mengfan Zhao; Di Deng; Hui Liu; Rui Guo; Jun Wu; Yu Hao; Mingrui Yang (Viruses)
Infection with influenza A virus (IAV) may trigger excessive inflammatory responses, leading to severe viral pneumonia and accelerating disease progression. Therefore, controlling these excessive inflammatory responses is crucial for the prevention and treatment of pneumonia caused by IAV. Berberine (BBR), an isoquinoline alkaloid extracted from traditional Chinese medicine, possesses extensive pharmacological activities. However, its immunoregulatory effects and molecular mechanisms in the context of IAV infection require further investigation. This study explored the impact of BBR on macrophage pyroptosis and inflammatory responses induced by IAV infection. Our findings revealed that BBR effectively inhibits the release of IL-1β and TNF-α induced by IAV infection and suppresses gasdermin D (GSDMD)-mediated pyroptosis in a dose-dependent manner. Further research indicates that BBR alleviates macrophage pyroptosis and inflammatory responses in IAV-infected cells by reducing the release of mitochondrial reactive oxygen species (mtROS), inhibiting mitochondrial antiviral signaling protein (MAVS) expression and blocking the activation of the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome. Experiments using siRNA to knockdown MAVS further confirmed the pivotal role of MAVS in BBR’s inhibition of IAV-induced macrophage pyroptosis. This study provides a scientific basis for the application of BBR as an anti-inflammatory drug in the treatment of inflammatory diseases caused by IAV infection and directs future research endeavors.